KOMUNITAS MOTOR SUPERMOTO OWNER GROUP (SMOG) SIAK - Rifardi "; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Motorcycle community is a social group that occurs in modern societies. In this case the role of social groups should have the capital to maintain and develop the social group, where the role of such capital must be owned by every member of the social group, in this case it is a social group motorcycle community. Motorcycle community in this case is a social phenomenon to exist in modern society. This study analyzes the activities / events and the role of capital in the motorcycle community Supermoto Owner Group (SMOG) in Siak. Where the role will be discussed by the economic capital, social capital, symbolic capital, and cultural capital, will then discuss how the strategy to develop the motorcycle community and discuss public perceptions surrounding the motorcycle community, especially motorcycle community Supermoto Owner Group (SMOG) Siak. The theory used in this study is of capital (Economic, Social, and Cultural Symbolic) habitus and Arena. The data analysis was done in answer to the problem is to use qualitative research with descriptive analysis in order to deepen a social phenomenon and then draw conclusions. This research is presented in narrative form qualitatively. Sources of data obtained through the study of literature, books, magazines, newspapers, as well as the articles. Data collection techniques used in this research is the direct observation, interviews and documentation. The sampling technique used was purposive sampling technique. Where the amount informants about 10 people were divided into two parts so that five informants came from motorcycle community members Supermoto Owner Group (SMOG) Siak, then 5 from the surrounding community. From these results motorcycle communitySupermoto Owner Group (SMOG) Siak activities that are positive for them and also the surrounding community. Then motorcycle communitySupermoto Owner Group (SMOG) Siak have also shown the role of capitals, where the economic capital, social, symbolic and cultural which has been owned by each member or the community itself. Then the motorcycle community presence Supermoto Owner Group (SMOG) Siak it also presents the pro and contra in the eyes of the surrounding community. As not all of the view that both these communities.Keywords: Community, Capital (Economic, Social, and Cultural Symbolic), Strategy, Perception